PENOLOGI PENGAYOMAN: Sebuah Tinjauan Pemidanaan dalam Integrasi Ilmu Pengetahuan - Akmal, Fachrurrozy (Fakultas Syariah Institut Agama Islam Negeri (IAIN) Pontianak, 2020)
This study aims to analyze the punishment pattern in the national penal system. This is a consequence of the involvement of science in the penal concept in Indonesia with a focus of research to understand the role of science in addressing the challenges related to policymaking, fostering treatment, as well as prisoner guidance which is carried out by the technical implementation unit (UPT) within the Directorate General of Corrections. Based on the analysis, the method used in this paper is juridical normative with positive legal approaches and descriptive-analytical research. The discussion in this paper states that punishment pattern in Indonesia refers to the principle of protection that functions in providing a sense of security for all parties both perpetrators of crime, victims and especially the community. The principle of punishment in the protection always seeks to see the success of a pattern of treatment within the framework of behavioral change of a person's criminality before the reintegration into society. Leadership and power of correctional institutions in the concept of aegis penology are oriented to the creation of productive and democratic spaces. The success of leadership in a punishment process is also determined by the transparency of the discourses. The presence of science in treatment and guidance aims to prevent fallacy such as a tendency in the generalization of different prisoner characters in the correctional process. Besides, the presence of knowledge in the guidance determines the pattern and appropriate treatment to correctional clients.